Large-scale fire whirl and forest fire disasters: Awareness, implications, and the need for developing preventative methods - Darwish Ahmad, Adnan; Akafuah, Nelson K.; Forthofer, Jason; Fuchihata, Manabu; Hirasawa, Taro; Kuwana, Kazunori; Nakamura, Yuji; Sekimoto, Kozo; Saito, Kozo; Williams, Forman A. (Frontiers in Mechanical Engineering, 2023)
The authors are a team of fire whirl researchers who have been actively studying fire whirls and large-scale wildland fires by directly observing them through fire-fighting efforts and applying theory, scale and numerical modeling, and artificial intelligence. The paper will discuss the mechanisms of the Great-Kanto-Earthquake-generated Hifukusho-Ato Fire-whirl (HAFW), fire spreading over live conifer fuels, and the role of slow rotations observed during recent forest fire fire-fighting efforts. The team conducted the studies with scaling techniques to reconstruct hazardous large-scale fires in the laboratory, fundamental theory to translate these findings into a basic understanding of combustion science and fluid dynamics, and numerical model simulations. The HAFW occurred in downtown Tokyo on September 1, 1923, and claimed over 38,000 deaths within 15 minutes (Soma and Saito, 1991; Kuwana et al., 2007). Based on knowledge gained through these studies and observations, this paper discusses possible methods to effectively prevent the occurrence of HAFW or mitigate and control HAFW when it occurs. In addition, this paper also discusses large-scale slow rotations observed during recent forest fires, which might have been responsible for the injuries and deaths of experienced firefighters. The interdisciplinary expert team addresses comprehensive practical methods to control and mitigate the above-mentioned large-scale fire whirls and shares some safety concerns on forest fires with knowledge of thermodynamics, chemical kinetics, fluid dynamics, design, and practical fire-fighting experience. We believe the topic of this study is timely and important when the frequency and intensity of large-scale forest fires and fire whirls have increased, possibly due to the continuing global warming trend and human-induced changes in fuels. This paper’s nature is review, case study, sharing new ideas, public safety, and well-being, which were made possible by progress in science.